Three new species of abdominal shrimp parasites (Crustacea: Isopoda: Bopyridae: Hemiarthrinae) from the Indo-West Pacific - An, Jianmei; Chen, Ruru; Paulay, Gustav (Zootaxa, 2020)
Three new species of the parasitic isopod subfamily Hemiarthrinae Markham, 1972 are described. Allodiplophryxus unilateralis n. sp. is described from Western Australia, infesting the palaemonid shrimp Jocaste lucina (Nobili, 1901), and females differ from the only other species in the genus in possessing six pleomeres, an asymmetrical first oostegite and pleopods restricted to the short side of the body. Loki athanus n. sp. is described from Madagascar, infesting the alpheid shrimp Athanas parvus de Man, 1910, and females differ from the only other species in the genus in possessing well-developed lateral plates on pleomere 4 and four pairs of uniramous pleopods. Hemiarthrus alphei n. sp. is described from French Polynesia, infesting the alpheid shrimp Alpheus crinitus Dana, 1852, and females differ from the four other known Hemiarthrus species in having pleomeres with well-developed, symmetrical lateral plates, a barbula with three pairs of projections and a pointed pleotelson. Keys to species of Hemiarthrus and all genera of the Hemiarthrinae are presented.